Analysis of Road Damage in Majalengka Regency, West Java - Sunowo, Muhamad Reyhan; Maulana, Ickbal; Bestari, Reyhan Yogas; Sugiyanto, Martinus Agus; Novriani, Shinta (Indonesian Journal of Multidisciplinary Science, 2025)
Road damage on the Maja-Sukahaji route, exacerbated by overloaded vehicles, compromises safety and pavement longevity. This study evaluates flexible pavement conditions using the Pavement Condition Index (PCI) and recommends cost-effective treatments. Visual surveys and PCI assessments were conducted across 10 segments (100 m each), analyzing damage types, severity, density, and deduct values. Treatments were prioritized using Bina Marga guidelines, and costs were calculated via the Majalengka AHSP. Segments 6 and 7 were in poor condition (PCI 51–54), while segment 10 failed (PCI 1). Recommended interventions included patching (P5), paving (P2), and leveling (P6), with a total budget of Rp. 142,381,914.12. The study offers a replicable framework for localized road maintenance, combining PCI analysis with budgetary precision, and underscores the need for proactive repairs to prevent further deterioration. Future research should explore predictive maintenance models and alternative materials (Fadillah et al., 2024; Mutoharoh et al., 2022).